Men having sex with men and the HPV vaccine in France: A low vaccine coverage that may be due to its infrequent proposal by physicians. Issue 9 (24th February 2020) - Petit, Benoit; Epaulard, Olivier
Highlights: MSM vaccine coverage was low this study, and is probably lower in the MSM population. HPV vaccine perceptions were positive; most unvaccinated participants would accept it. Low vaccine coverage may primarily result from an infrequent proposal by physicians. Abstract: Introduction: In France, the human papilloma (HPV) vaccine is recommended to all female adolescents, and since 2016 to men having sex with men (MSM) under the age of 27. Here, we aimed to explore HPV vaccine coverage in adult MSM living in France. Methods: We elaborated an anonymous online questionnaire targeting MSM and disseminated it between October 7, 2018 and January 15, 2019 by various means, including a Facebook® discussion forum for pre-exposure prophylaxis (PrEP) users. Results: Overall, 2094 participants completed the questionnaire (mean age 35.4 ± 11 years); 25.8% were in the age class targeted by the HPV vaccine recommendation; 16.1% were in a PrEP program. On a 1–10 scale, they evaluated being "in favor of vaccination" at a median of 10, and general vaccine usefulness and harmfulness at medians of 10 and 2, respectively; 62.4% considered that the HPV vaccine was rather not or not at all dangerous. Those using PrEP had better perceptions of vaccination in general and of the HPV vaccine in particular. For the 1728 participants with a family physician, he/she had proposed the HPV vaccine in 9.9% of cases (9.1% of those in the targeted age class [<27 years]). Overall, 1994 knew their HPV vaccine status; 8.0% had received at least 1 dose of the vaccine, including 17.9% of those in the targeted age class (and 52.2% among the 40 participants in this age group who received PrEP). When the 1935 participants who declared to be unvaccinated against HPV were asked whether they would accept to be vaccinated, 34.4% answered "rather yes" and 45.5% "definitely yes". Conclusion: HPV vaccine coverage is low among French MSM. Our results suggest that this trend has more to do with the infrequent proposals made by clinicians than with negative vaccine perceptions.